Disparity in the Considerations of Judges in Deciding Divorce Disputes in Religious Courts and District Courts - Dodon Alfiander (Institut Agama Islam Negeri Batusangkar, 2022)
This paper aimed at exploring judges’ disparity in deciding divorce disputes in religious courts and district courts. Disparity is not only the differences in legal subjects that obey the absolute competence of different judicial environment but also the norms that serve as guidelines. This research is empirical juridical research with primary data namely judges’ decision and the results of judges’ interview. This research found that there were several disparity differences between religious and district judges in deciding divorce disputes. First, the considerations of district court judges were oriented to the aspect of legal certainty over juridical considerations. Second, besides paying attention to legal certainty aspects, the panel of judges at religious courts also considered religious aspects in making decision. Consideration of the rules of Islamic law has a very important role for judges in making decisions.